Reimagining the tour operator industry in the post-pandemic period: Is the platform economy a cure or a poison? - Kristína Pompurová; Ľubica Sebova; Petr Scholz (Cogent Business & Management, 2022)
This study considers the relationship of the tour operators to the tourism platform services in the context of a COVID-19 post-pandemic recovery. The findings are based on semi-structured interviews with representatives of Slovak tour operators' businesses. The results show that the platform economy is not perceived as a poison for the industry. Specialised tour operators are less open to potential cooperation than organisations with the mass product, which are especially likely to use platform information and incorporate platform food-related services into packagded tours enriched with authentic experiences. Platform economy thus presents for willing tour operators a chance to differentiate themselves, open uncontested market space and survive in a competitive post-pandemic period. In this context, legislation development is required.
Keywords: 650; platform tourism services; post pandemic period; sharing economy; tour operators